THE ENZYMATIC HYDROLYSIS AS A PROMISING METHOD OF PROCESSING LACTOSE-CONSISTING RAW MATERIALS - Andrew Georgievich Khramtsov; Alexey Dmitrievich Lodygin; Natalya Andreevna Perevyshina; Eduard Mikhailovich Iordanyan (Вестник Северо-Кавказского федерального университета, 2022)
Modern methods of lactose hydrolysis and prospective of their enforcement are discussed. Results of studying of lactose enzymatic hydrolysis in lactose solutions and whey permeate are given.